Neutropenia and neutrophil‐to‐lymphocyte ratio in a healthy Korean population: race and sex should be considered. (28th March 2016) - Kweon, O. J.; Lee, M.‐K.; Kim, H.‐J.; Chung, J.‐W.; Choi, S.‐H.; Kim, H. R.
Summary: Introduction: We evaluated the prevalence and severity of asymptomatic neutropenia in a healthy Korean population according to sex and age. We explored normal neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) in an asymptomatic Korean population and the association of these ratios with biomarkers related to inflammation, rheumatoid disease, and glucose metabolism. Methods: We analyzed complete blood cell counts in 83 740 subjects who participated in a routine health check‐up program. NLR and PLR were compared to age, rheumatoid factor, C‐reactive protein (CRP), erythrocyte sedimentation rate, hemoglobin A1c, and fasting glucose levels. Results: Of the entire study population, 7.48% exhibited neutropenia; 8.61% of females and 6.69% of males. The neutropenia was more severe in females compared to males ( P < 0.01). Median NLR and PLR values were 1.53 and 121.07, respectively. An inverse relationship was observed between NLR and age, but no differences were seen between sexes. CRP, erythrocyte sedimentation rate, and fasting glucose level were significantly correlated with NLR. Conclusion: Our data indicate that the normal range of absolute neutrophil counts should be adjusted and cutoff values for neutropenia should be re‐established according to sex and race. NLR and PLR cutoff values for disease evaluation should be established separately according to race and age.